The Pyrophosphate Heart Scintigram in Children with Progressive Muscular Dystrophy - Duška, F.; Nesvadba, Z.; Ždánský, P.; Novák, J.; Kubíček, J.; Kafka, P.; Vižda, J.; Mazurová, Y. (Nuklearmedizin - NuclearMedicine, 1984)
A pyrophosphate heart scintigram was obtained in 16 boys with progressive muscular dystrophy Duchenne. All of them showed pathological ECG findings and high plasma levels of CK, AST, ALT and LD. In 4 patients the scintigram was distinctly positive and in further 3 it reached borderline values. The remaining 9 boys had normal scintigraphic findings. Those with a positive heart scintigram had very high plasma levels of the enzymes under study which was suggestive of current progression of the disease. There was, however, no relation between heart scintigraphy and the affliction of the skeletal muscles expressed by means of an index.